2009
DOI: 10.3201/eid1502.081028
|View full text |Cite
|
Sign up to set email alerts
|

Novel Human Parechovirus from Brazil

Abstract: Human parechoviruses (HPeVs) were detected by reverse transcription-PCR in 16.1% of 335 stool samples from children <6 years of age with enteritis in Salvador, Brazil. Whole genome sequencing of 1 sample showed a novel HPeV that has been designated as HPeV8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
59
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 14 publications
3
59
0
Order By: Relevance
“…The results showed that four different HPeV genotypes, HPeV1 to HPeV4, were present among Thai infants and children with acute gastroenteritis, and more than a half of the strains detected belonged to HPeV1. That finding was in good agreement with the findings of previous studies, which reported that HPeV1 was predominant over other the HPeV genotypes found in patients with acute gastroenteritis (3,4,6,9).…”
Section: Discussionsupporting
confidence: 83%
“…The results showed that four different HPeV genotypes, HPeV1 to HPeV4, were present among Thai infants and children with acute gastroenteritis, and more than a half of the strains detected belonged to HPeV1. That finding was in good agreement with the findings of previous studies, which reported that HPeV1 was predominant over other the HPeV genotypes found in patients with acute gastroenteritis (3,4,6,9).…”
Section: Discussionsupporting
confidence: 83%
“…Direct involvement of ␣ v integrins in the infectious entry of HPEV1 was further confirmed by overexpression of human ␣ v ␤ 1 and ␣ v ␤ 3 integrins in Chinese hamster ovary (CHO) cells, allowing successful virus infection (74). There are no reports yet on the identification of receptors for the HPEV types lacking the RGD motif (HPEV3, HPEV7, and HPEV8) (19,39,51).…”
mentioning
confidence: 99%
“…Direct involvement of ␣ v integrins in the infectious entry of HPEV1 was further confirmed by overexpression of human ␣ v ␤ 1 and ␣ v ␤ 3 integrins in Chinese hamster ovary (CHO) cells, allowing successful virus infection (74). There are no reports yet on the identification of receptors for the HPEV types lacking the RGD motif (HPEV3, HPEV7, and HPEV8) (19,39,51).Although the crystal structures of several picornaviruses have been determined (3,26,34,35,44,57,59,65,68,72) and the receptor interactions have been studied in detail by X-ray crystallography, electron cryo-microscopy (cryo-EM), and threedimensional (3D) image reconstruction (6,9,23,31,32,47,83), there is no structural information available for the parechoviruses or parechovirus-receptor complexes. Here, we compare the binding of ␣ V ␤ 3 and ␣ V ␤ 6 to HPEV1 in vitro by biochemical assays and determine the structures of HPEV1 and the corresponding HPEV1-integrin complexes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Enterovirus contains Ͼ250 recognized types that can infect humans, including poliovirus (PV), echovirus (E), coxsackie A virus (CV-A), coxsackie B virus (CV-B), and rhinovirus (RV). The genus Parechovirus consists of two species, Ljungan virus and Human parechovirus (HPeV), which at present contains 16 recognized genotypes (1)(2)(3)(4)(5)(6)(7)(8). Compared to EV genotypes, which circulate simultaneously, only a few different HPeV genotypes circulate in the human population: HPeV1, -3, and -4 are the most dominant; HPeV5 and -6 are found circulating at a lower frequency; and the most recently discovered types, HPeV7 to -16, are hardly found circulating in (Western) populations.…”
mentioning
confidence: 99%